Perancangan Sistem Informasi Pelayan Publik di Era Pandemi Covid-19 - Siti Fatonah (JOPPAS: Journal of Public Policy and Administration Silampari, 2021)
ABSTRACT This study aims to find out how to plan a public service information system in the era of the covid-19 pandemic. The research method is an associative type of research which aims to analyze the quality of reliability, responsiveness, assurance, empathy, and physical evidence. The results of the study show that public services are efforts carried out by individuals to agencies that play a role in meeting the needs of the community. The existence of the COVID-19 pandemic has an impact on employee performance in the field of public services which is not optimal. Especially in the attitude of public service employees who are in the District Office, since the pandemic, the performance seen from the indicators of public service attitudes has not been optimal. In this context, all activities are limited and required to apply the health protocols recommended by the government. Employees do work from home online with the demands of new normal era public service protocol procedures. Subdistrict employees also work according to shifts which are divided into several days taking into account health protocols. The conclusion of the research is that the implementation of e-government is able to make a positive contribution to the public service process. Keywords: Information Systems, Publik Service